2013
DOI: 10.1149/ma2013-02/6/463
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition and Dissolution of Magnesium Metal in Various Ether-Based Electrolytes

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…For example, Mg redox behavior has been observed in an IL solution of Mg(ClO 4 ) 2 or MgCl 2 , although their current densities were significantly lower than those for RMgX-dissolved ILs. 11 Some organic solvents that enable redox of Mg are less volatile than THF; these include 2-methyl-tetrahydrofuran, 12 and ethyleneglycol dimethylethers (glymes), [13][14][15] where Mg halides and hydrides were dissolved. Notably, glymes have boiling points above 150 • C and are relatively safe at room temperature.…”
mentioning
confidence: 99%
“…For example, Mg redox behavior has been observed in an IL solution of Mg(ClO 4 ) 2 or MgCl 2 , although their current densities were significantly lower than those for RMgX-dissolved ILs. 11 Some organic solvents that enable redox of Mg are less volatile than THF; these include 2-methyl-tetrahydrofuran, 12 and ethyleneglycol dimethylethers (glymes), [13][14][15] where Mg halides and hydrides were dissolved. Notably, glymes have boiling points above 150 • C and are relatively safe at room temperature.…”
mentioning
confidence: 99%
“…Deposition of elemental Mg without THF and/or RMgX has been reported. [18][19][20][21][22][23][24] Cheek et al showed Mg deposition redox behavior at room temperature in an IL dissolving Mg(ClO 4 ) 2 or MgCl 2 , although their reduction currents were significantly lower than that in RMgX-containing ILs. 18 Abe et al demonstrated the reversible deposition/dissolution cycle of Mg with high coulombic efficiency in 2Me-THF where MgBr 2 dissolved.…”
mentioning
confidence: 99%
“…19 In addition, they also showed that some kinds of glyme solution, where MgCl 2 and AlCl 3 were dissolved, gave reversible deposition/dissolution behavior at room temperature. 20 Nevertheless, the abovementioned Mg salts contain halide anions, which can form halogen gas through anodic oxidization. 18 Because halogen gases carry a high environmental burden, non-halide anion electrolytes such as Mg(Tf 2 N) 2 are favorable.…”
mentioning
confidence: 99%